Opettajaopiskelijoiden kokemuksia opettajien osaamisvaatimuksista terveysalalla. - TIKANOJA, MINNA; KOIVULA, MEERI (Hoitotiede, 2020)
The competence requirements of teachers in health-care education are wide-ranging; they change with the social situation, education and health care systems, the needs of the population, and technical and scientific developments. In teacher training in the practice of health care education, teacher students' face the challenges of teaching, but there is little information about their experiences in teacher training. The purpose of this study was to describe student teachers' experiences with teachers' competence demands during their teaching training in health care education. The data consist of web conversations, which 29 student teachers had during their teacher training. They completed their teacher training in eight different universities of applied sciences and two secondary educational institutions in Finland. The data were analyzed using the inductive content analysis method. Teacher students' experiences with teachers' competence requirements in health care education are described by teaching in the field of substance, managing aspects of teaching, student centered pedagogy, ethical conduct, work community competence, social skills, taking care of one' own well-being, and the continuous development of one' own competence. In teacher training, teacher students' experiences with teachers' competence requirements were more limited than in previous studies. The results of the research can be utilized in teacher education in health sciences and in the development of teacher training in the health sector.